2019
DOI: 10.5194/se-10-663-2019
|View full text |Cite
|
Sign up to set email alerts
|

Relative timing of uplift along the Zagros Mountain Front Flexure (Kurdistan Region of Iraq): Constrained by geomorphic indices and landscape evolution modeling

Abstract: Abstract. The Mountain Front Flexure marks a dominant topographic step in the frontal part of the Zagros Fold–Thrust Belt. It is characterized by numerous active anticlines atop of a basement fault. So far, little is known about the relative activity of the anticlines, about their evolution, or about how crustal deformation migrates over time. We assessed the relative landscape maturity of three along-strike anticlines (from SE to NW: Harir, Perat, and Akre) located on the hanging wall of the Mountain Front Fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 84 publications
(164 reference statements)
2
27
0
Order By: Relevance
“…(b) Schematic cross section that shows the structural setting of the Dinarta syncline, where the growth strata of the Bai‐Hasan formation is preserved. The cross section is based on Zebari and Burberry (2015) and Zebari et al (2019). (c) Geologic map of the Dinarta syncline that shows a major and a minor reverse fault, and locations of filed photographs.…”
Section: Kinematics Of Shorteningmentioning
confidence: 99%
“…(b) Schematic cross section that shows the structural setting of the Dinarta syncline, where the growth strata of the Bai‐Hasan formation is preserved. The cross section is based on Zebari and Burberry (2015) and Zebari et al (2019). (c) Geologic map of the Dinarta syncline that shows a major and a minor reverse fault, and locations of filed photographs.…”
Section: Kinematics Of Shorteningmentioning
confidence: 99%
“…Geologically, the study region in the Zagros FTB mainly consists of limestone and sandstone rocks aged from the late Cretaceous to the Palaeocene. The Zagros FTB is located along a section of the Arabian and Eurasian plates (Talebian & Jackson 2004) and is characterised by numerous active anticlines atop of a basement fault (Zebari et al 2019). The structurally complex joints, folds, slips, faults, and fractures reflect the dynamic nature of the regional tectonics.…”
Section: Study Areamentioning
confidence: 99%
“…2018), and the Zagros mountains in northern Iraq (Obaid & Allen 2017; Obaid & Allen 2019; Zebari et al . 2019). For instance, Yıldırım (2014) has noted that the geomorphic indices are compatible with the general relief of the mountain front and differential uplift along the fault zone of central Anatolia.…”
mentioning
confidence: 99%
“…In recently active tectonic areas, the topography of the land surface is an accurate reflection of the underlying structure and its interaction with surface processes [11]. [6]); [7,8]. The black rectangle represents the study area plotted in Figure-3, and the magnitude of the 102 earthquakes is indicated by the diameter of the colored circles.…”
Section: Tectonic and Structure Settingmentioning
confidence: 99%